(untitled) (Veterinary Science, 2017)
The authors report the results of the use of a hybrid external skeletal fíxator for the treatment of a Salter-Harris fracture, type 1, of the distal epiphysis of the tibia in a fourmonth- old female retriever. Due to the reduced distance between the articular surface and that of the fracture , the authors decided to combine I1izarov’ s and Kirchener-Ehmer’ s principies of external fixation 10 secure the stability of the reduced fracture. After five days, the retriever started to lean on the affected limb and the fixator was removed thirty days after the surgery. The combination of the benefits offered by each of the fixation systems proved to be optimal for the repair of this Salter-Harris fracture, type 1.